ZISWAF Management Strategy in Creating Community Welfare at Jogokariyan Mosque - La Abdul Zayl; La Ode Masri; Risno Ibrahim; Arif Sevfri Diansyah; Muhammad Almin Kaliky; Mohammad H. Holle; Ahmad Sholehuddin Suryanullah (Transpublika Publisher, 2025)
The use of mosques in Islamic history has been closely linked to supporting the interests of the community, not only in terms of worship, but also in terms of management that promotes the welfare of the community. This foundation is recognised by the management of Jogokariyan Mosque in optimising its management to move the mosque out of a cycle where its role is not fully utilised for community economic development. One of the management strategies implemented by the Jogokariyan Mosque management is innovation in organising the potential of ZISWAF as philanthropy in Islam, which is crucial for supporting the distribution of social justice. Therefore, this study aims to deeply explore the ZISWAF management strategies implemented by the management at Jogokariyan Mosque, who have dared to transform their ideas in developing the mosque's role in community life. A qualitative research method with a case study approach was used in this study, and this methodology was selected based on calculations to obtain results in the research. Based on the results of the research conducted, the findings indicate breakthroughs in the management of ZISWAF by the administrators at Jogokariyan Mosque, who have reformed strategies in design, collection, distribution, accountability, and evaluation to enhance the mosque's contribution to community life. These efforts have also impacted the fulfilment of basic needs and promoted economic sustainability to achieve community well-being.